Is sickle cell anemia a risk factor for severe dental malocclusion? - Cyrene Piazera Silva COSTA; Halinna Larissa Cruz Correa CARVALHO; Soraia de Fátima Carvalho SOUZA; Erika Bárbara Abreu Fonseca THOMAZ (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to investigate possible associations between sickle cell anemia (SCA) and the severity of dental malocclusion (MO). This was a retrospective cohort study of 93 individuals with SCA (G1) and 186 individuals without the disease (G2). SCA patients were randomly selected by a simple draw from patients treated in the Centro de Hematologia e Hemoterapia do Maranhão (HEMOMAR) in northeastern Brazil. Patients aged between 16 and 60 were included after being tested for the hemoglobin S gene. G2 consisted of individuals living in the same residence as the patients. The Dental Aesthetic Index (DAI), as well as some morphological deviations not included in DAI, were used for the orthodontic evaluation of MO. Poisson regression with robust variance adjustment was employed to estimate relative risk (RR). In the multivariate analysis, SCA was associated with moderate (RR = 1.36) and very severe MO (RR = 8.0). SCA is correlated with anterior tooth loss (RR = 1.94), anterior spacing (RR = 1.66), overjet (RR = 1.87), anterior crossbite (RR = 1.94), and open bite (RR = 1.94). Thus, SCA is a risk factor for moderate and very severe MO.